2018
DOI: 10.1002/pc.24819
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Sustainable Design to Develop Polypropylene and Unsaturated Polyester Resin Polymer Composites From Waste of Major Polluting Industries and Investigation on Their Physicomechanical and Wear Properties

Abstract: A novel concept of using Nutraceutical Industrial Coriander Seed Spent (NICSS) and Congo red (CR) dye adsorbed onto NICSS (CR‐NICSS) as filler materials to fabricate polypropylene (PP) green thermoplastic composites and unsaturated polyester resin unsaturated polyester resin (USP)/CR‐NICSS and USP/NICSS composites is presented. To maximize the adsorption of CR on NICSS and to study the influence of five parameters viz, process time, temperature, initial concentration of dye, adsorbent dosage and pH of the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
(41 reference statements)
0
20
0
Order By: Relevance
“…The better approach for the disposal of the waste process materials could be to use the current method which is under development which is to fabricate thermosets and thermoplastics. Work on which is in progress in our laboratory and some interesting results obtained are reported elsewhere [64,65].…”
Section: Regeneration Of the Adsorbent And Cost Analysismentioning
confidence: 92%
See 2 more Smart Citations
“…The better approach for the disposal of the waste process materials could be to use the current method which is under development which is to fabricate thermosets and thermoplastics. Work on which is in progress in our laboratory and some interesting results obtained are reported elsewhere [64,65].…”
Section: Regeneration Of the Adsorbent And Cost Analysismentioning
confidence: 92%
“…Our research school is the first to report the use of NIS as filler material in the fabrication of thermoplastic and thermoset composites [33,[54][55][56][57][58][59][60]65] and for the use as effective adsorbents for remediation of Congo red, methylene blue and ethidium bromide dyes [32,53,64]. Despite myriad research papers reported the use of low-cost agriculture waste as biosorbent for the remediation of toxic dyes; very limited information is available about the use of dye adsorbed biosorbent commonly known as "sludge".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of increased stringencies imposed on pollution, a novel approach has been developed to use the dye-adsorbed biosorbent generated waste to be used as a filler material for the fabrication of thermosets and thermoplastics. The work in this direction is in progress in our research laboratory [32,35].…”
Section: Regeneration Of the Adsorbent And Cost Analysismentioning
confidence: 99%
“…The vast amount of published reports on adsorption of dyes using low-cost biological materials did not indicate any methods for the reuse of resulting "sludge". A feasible solution to dispose off the dye-adsorbed "sludge" is to incorporate the same in petroleum-based non-biodegradable thermoplastics thereby generate green composites lowering the use of plastics and reducing carbon footprint [32,35]. By combining lignocellulosic materials with plastics, it is possible to get many environmental friendly benefits including making of light weight final product, lowering the manufacturing machinery erosion, cost reduction, biodegradability and prevention/minimization of burnt residue production or toxic by-products.…”
Section: Introductionmentioning
confidence: 99%